Damselflies Found in Batu Putu Waterfall Nature Park - Imaniar, Lisana Husna; Haryati, Yayuk; Wahyuni, Diana Putri; Ningrum, Dita Puspita; Mahendra, Puput Eka; Sinurat, Esra Maduma; Sari, Dian Anggria (MAXIMUS: Journal of Biological and Life Sciences, 2024)
Batu Putu Waterfall Nature Park is one of the many local tourist destinations in Bandar Lampung City, yet biodiversity data of it is so scarce. Considering the fact that this area focused on its waterfall’s natural beauty and the river alongside it, it was deemed important to conduct a study to better understand local organism that have close relationship with freshwater bodies. This study aims to determine the damselfly species found in Batu Putu Waterfall Nature Park. Specimens were captured using insect nets along the waterfall and riverbed during the daytime in fine weather. These specimens were then preserved in an insectarium and later identified using taxonomic keys. The result found at least four species of damselflies were living in Batu Putu Waterfall Nature Park area. Those are Euphaea variegata, Vestalis luctuosa, Prodasineura sp, and Elattoneura sp.